Transformasi Teritori berdasarkan Kegiatan Pengunjung di Lapangan Gasibu - Bachtiar, Jasmine Chanifah U (RUAS, 2023)
Personal space (proxemics) in public spaces should be considered essential to keeping the personal area separate from others. Meanwhile, privatization in public space will divide the area into small personal spaces due to the unclear form of territory in personal spaces. This study will identify and reveal the pattern of visitors’ territory transformation based on visitors’ activities in Lapangan Gasibu, Bandung. The data will be collected through observation and a survey on a weekday (Thursday) and weekend (Saturday). Then, the data will be analyzed using a descriptive analysis method based on mapping activities in the area. The result shows three transformations of spaces based on visitors’ activities and territories in Lapangan Gasibu. The pattern of transformation shows some areas of territorial spaces with unclear protection but need to avoid personal conflicts and some shared areas with low protection of territories. Thus, the thoughtful design of public spaces and physical facilities should be taken into consideration. This result is expected to be taken as a design reference for designing and creating comfortable public spaces that meet the need for personal spaces and activities.